Foreign trade and trade defense in Brazil: A report for the period 2003-2009 - Garrido da Costa Lima, Pedro (2010)
The essay outlines some essential elements of foreign trade and trade remedies policy in Brazil during the period 2003-2009 –that is the two consecutive administrations of President Lula da Silva. The authors show that the increase in trade flows and changes in the Brazilian exports does not reflect a coherent management of a protectionist policy even in the current international economic crisis.